PENGUKURAN KINERJA EFISIENSI BADAN PEMERIKSA KEUANGAN DENGAN MENGGUNAKAN DATA ENVELOPMENT ANALYSIS Studi Kasus Pada Kantor Perwakilan BPK Tahun 2015 - Widya, Talisa Noor (Jurnal Ilmiah Mahasiswa FEB, 2017)
The objective of this research is to understand the efficiency of Provincial Representative Offices of BPK in 2015 using Data Envelopment Analysis. This quantitative descriptive study uses 34 BPK provincial representative offices as the research object. The data were obtained from documentation of BPK. The inputs are audit budget realization and the number of auditors. The outputs are the number of audit reports (LHP) and the number of on- time audit reports. This study uses variable returns to scale (VRS) assumption with output orientation. The result of the DEA shows that there are 11 efficient offices. Large-sized offices tend to be more efficient than their small-sized counterparts. Efficiency tends to be caused by a high number of LHP, meanwhile inefficiency tends to be caused by a high number of auditors. Keywords:Â  Performance measurement, Data Envelopment Analysis, efficiency, Audit Board of Indonesia.